2018
DOI: 10.1093/poq/nfy004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Voter Decision Strategies in Political Behavior and Public Opinion Research

Abstract: The 2008 presidential election was an historic moment in American politics for many reasons, not least of which was the Democratic Party selecting an African American as its nominee. Speculation about how racial prejudice might affect Barack Obama's candidacy was widespread, and varied from proclamations that we now live in a "post-racial society" to condemnations that race would cost him the election. For scholars interested in the possible implications of racism for American politics, Obama's candidacy and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…Finally, many adolescents demonstrated a stout understanding of Trump’s social and political policy agenda, and this knowledge intersected with their own values and political opinions in their appraisal of the president. These broad factors that formed the foundation of youth (dis)approval ratings align with those identified by an extensive body of political science, which has found that adults’ views of politicians are rooted in their understanding of the politician’s policies and agenda and evaluation of their personal attributes and linked to individual’s own personal experiences (Lau et al, ). Thus, the processes and factors underlying youth’s ratings of political leaders may mirror those seen among adult voters.…”
Section: Discussionmentioning
confidence: 78%
“…Finally, many adolescents demonstrated a stout understanding of Trump’s social and political policy agenda, and this knowledge intersected with their own values and political opinions in their appraisal of the president. These broad factors that formed the foundation of youth (dis)approval ratings align with those identified by an extensive body of political science, which has found that adults’ views of politicians are rooted in their understanding of the politician’s policies and agenda and evaluation of their personal attributes and linked to individual’s own personal experiences (Lau et al, ). Thus, the processes and factors underlying youth’s ratings of political leaders may mirror those seen among adult voters.…”
Section: Discussionmentioning
confidence: 78%
“…We include controls for race and gender given, not least, their potential association with decision strategies. Lau et al (2018) found that women were more likely to prefer the rational choice model, while minorities were more likely to prefer the fast and frugal and confirmatory models.…”
Section: VIImentioning
confidence: 91%
“…The full list of survey items, corresponding scales, and descriptive statistics are included in Appendices E and B, respectively (see Supplementary Materials). Detailed analysis demonstrating the reliability and discriminant validity of the decision strategy subscales can be found in Lau et al (2018). Our experimental design also allows us to observe actual information search behavior, which is a crucial indicator of decision strategy (Lau & Redlawsk, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations